Chronic Anterior Pelvic Instability: Diagnosis and Management. Issue 7 (July 2017) - Stover, Michael D.; Edelstein, Adam I.; Matta, Joel M.
Abstract : Chronic anterior pelvic ring instability can cause pain and disability. Pain typically is localized to the suprapubic area or inner thigh; often is associated with lower back or buttock pain; and may be exacerbated by activity, direct impact, or pelvic ring compression. Known etiologies of chronic anterior pelvic ring instability include pregnancy, parturition, trauma, insufficiency fractures, athletics, prior surgery, and osteitis pubis. Diagnosis often is delayed. Physical examination may reveal an antalgic or waddling gait, tenderness over the pubic bones or symphysis pubis, and pain with provocative maneuvers. AP pelvic radiographs may demonstrate chronic degenerative changes at the pubic symphysis or nonhealing fractures. Standing single leg stance (flamingo view) radiographs can demonstrate pathologic motion at the pubic symphysis. CT may be useful in assessing posterior pelvic ring involvement. The initial management is typically nonsurgical and may include the use of an orthosis, activity modification, medication, and physical therapy. If nonsurgical modalities are unsuccessful, surgery may be warranted, although little evidence exists to guide treatment. Surgical intervention may include internal fixation alone in select patients, the addition of bone graft to fixation, or symphyseal arthrodesis. In some patients, additional stabilization or arthrodesis of the posterior pelvic ring may be indicated.